1986
DOI: 10.1159/000199268
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Absorption of Sulfated and Nonsulfated Bile Acids in Rat

Abstract: Absorption of sulfated and nonsulfated chenodeoxycholic and glycochenodeoxycholic acid was studied in the colon and the data were compared with the absorption rates in the ileum. Absorption of nonsulfated chenodeoxycholic acid in the colon was in the same range of magnitude as in the ileum. Glycochenodeoxycholic acid absorption in the colon was lower than in the terminal ileum. Sulfated bile acids were not absorbed in the colon. In the ileum, absorption of sulfated bile acids was significantly (p < 0.01) lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It has been shown that SLA is present in substantial quantities in human faeces and that the LA\SLA ratio was 2.1 [15]. It has further been suggested that lowered uptake of sulphated bile acids in the ileum, and lack of uptake in the colon, may contribute to their excretion [16]. Finally, studies with mice have shown that sulphated bile acids may inhibit colon carcinogenesis [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SLA is present in substantial quantities in human faeces and that the LA\SLA ratio was 2.1 [15]. It has further been suggested that lowered uptake of sulphated bile acids in the ileum, and lack of uptake in the colon, may contribute to their excretion [16]. Finally, studies with mice have shown that sulphated bile acids may inhibit colon carcinogenesis [17].…”
Section: Discussionmentioning
confidence: 99%
“…This is a general principle explained by the hydrophylic nature of glucurono-and sulfoconjugates which precludes their intestinal absorption [50]. Moreover, it was found recently that sulfated bile salts are poorly absorbed in the ileum and not at all in the colon [51], in contrast to unsulfated bile salts. Furthermore, Robben et al [15] reported that the 13 contamination of germ-free rats with sulfataseproducing anaerobic bacteria resulted in a 5-fold increase of the time required for the fecal excretion of the injected cholate sulfate, indicating a strong enhancement of the enterohepatic circulation of conjugates by hydrolytic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Sulfated bile acids, similar to the precursor bile acids, are able to induce bile flow and may play a protective role in cholestasis. 8,9 Sulfated bile acid amidates, in contrast to their nonsulfated, amidated bile acid precursors, do not undergo extensive enterohepatic circulation [10][11][12] because they are poor substrates of the intestinal sodium-dependent bile acid transporter that is present abundantly in ileal enterocytes. 12,13 It is therefore imperative to fully understand the uptake mechanisms of sulfated bile acid amidates in the liver.…”
mentioning
confidence: 99%